Nucleation Phase and Dynamic Inversion of the Mw 6.9 Valparaíso 2017 Earthquake in Central Chile. Issue 20 (28th October 2017) - Ruiz, S.; Aden‐Antoniow, F.; Baez, J. C.; Otarola, C.; Potin, B.; del Campo, F.; Poli, P.; Flores, C.; Satriano, C.; Leyton, F.; Madariaga, R.; Bernard, P.
Abstract: The Valparaiso 2017 sequence occurred in the Central Chile megathrust, an active zone where the last mega‐earthquake occurred in 1730. Intense seismicity started 2 days before the Mw 6.9 mainshock, a slow trenchward movement was observed in the coastal GPS antennas and was accompanied by foreshocks and repeater‐type seismicity. To characterize the rupture process of the mainshock, we perform a dynamic inversion using the strong‐motion records and an elliptical patch approach. We suggest that a slow slip event preceded and triggered the Mw 6.9 earthquake, which ruptured an elliptical asperity (semiaxis of 10 km and 5 km, with a subshear rupture, stress drop of 11.71 MPa, yield stress of 17.21 MPa, slip weakening of 0.65 m, and kappa value of 1.98). This earthquake could be the beginning of a long‐term nucleation phase to a major rupture, within the highly coupled Central Chile zone where a megathrust earthquake like 1730 is expected. Key Points: Valparaiso 2017 Mw 6.9 was preceded by repeaters and a slow slip event An intense seismicity was recorded before the mainshock The mainshock broke a small asperity of few kilometers